Planting with purpose : how farmers create a resilient food landscape - Ellingson, Stephen, 1962- (New York University Press, 2024)
Examines local food movement activism in a period of increasing climate chaos and neoliberal crisis, economic inequalities and political divisionsIn the face of numerous challenges, small-scale farming for local markets requires enormous courage and optimism. The decision to become a farmer often arises from a profound desire to uphold certain values and beliefs, driven by the moral and emotional motivations to contribute to a greater good.Central New York's local food market draws a unique cohort of individuals who see farming as more than just a livelihood; it is a way to define a good life and contribute to the well-being of the society they cherish. Their moral order revolves around shared beliefs in sustainability and stewardship of the land, emphasizing health and risk management, cooperation over competition, and a deep sense of justice. For these farmers, relationships and family ties are foundational to their work, creating a strong sense of community within the local food system.This book delves into the captivating world of local food markets in a "Rust Belt" region of the state, where 51 individuals representing 45 different farms, restaurants, agricultural non-profits, and local food retailers share their inspiring stories through conversations and interviews. Author Stephen Ellingson explores the intricate web of moral commitments, self-understandings, and emotional experiences that drive and sustain small-scale farming for the local food market. By amplifying the voices of these unsung heroes, it gives recognition to the crucial role they play in society and offers important insights into the values that underpin their contributions to the local food system.